Ursolic acid treats renal tubular epithelial cell damage induced by calcium oxalate monohydrate via inhibiting oxidative stress and inflammation. Issue 1 (1st January 2021) - Jia, Zhaohui; Li, Wensheng; Bian, Pan; Yang, Liuyang; Liu, Hui; Pan, Dong; Dou, Zhongling
ABSTRACT: Ursolic acid (UA) has been proved to have antioxidant and anti-inflammatory effects. However, it is not clear whether it has a protective impact on kidney damage induced by crystals of calcium oxalate monohydrate (COM). This work aimed to make clear the potential mechanism of UA protecting COM-induced kidney damage. The results manifested that high- and low-dose UA reduced COM crystals in COM rats' kidney, down-regulated urea, creatinine, and neutrophil gelatinase-associated lipocalin (NGAL) levels in rat plasma, declined kidney tissue and HK-2 cell apoptosis, inhibited Bax expression but elevated Bcl-2 expression. Additionally, UA alleviated renal fibrosis in COM rats, repressed α-SMA and collagen I protein expressions in the kidney and COM rats' HK-2 cells, depressed COM-induced oxidative damage in vivo and in vitro via up-regulating Nrf2/HO-1 pathway, up-regulated SOD levels and reduced MDA levels, down-regulated TNF-α, IL-1β, and IL-6 levels in vivo and in vitro via suppressing activation of TLR4/NF-κB pathway. In summary, the results of this study suggest that COM-induced renal injury can be effectively improved via UA, providing powerful data support for the development of effective clinical drugs for renal injury in the future. Graphical abstract: uf0001